Reşat Nuri Güntekin’in romanlarında eğlence kültürü - Aliji, Perver (My University, 2019)
19. yüzyıl, Osmanlı toplumunda sokak düzeninden aile hayatına, kılık kıyafetten eğlence biçimlerine kadar, yeniliğe ve değişikliğe açılan bir modernleşme dönemidir.

The 19th century is a period of modernization in Ottoman society, ranging from street life to family life, from costume to entertainment, to innovation and change.
Keywords: eğlence kültürü Reşat Nuri; entertainment culture; novel; Reşat Nuri; Reşat Nuri Güntekin, 1889-1956; roman; Turkish literature; Türk edebiyatı